Application of cyrotechnology techniques: a case study for the production, purification and characterization of humanized antibody secreted by NSO transfectoma - Cheah, S.H.; Dharshanan, S.; Chong, H.; Zamrod, Z. (Malaysian Society for Molecular Biology and Biotechnology, 2011)
Humanized monoclonal antibodies are widely used for diagnosis and treatment of cancer due to their reduced immunogenicity and high specificity. These valuable biopharmaceuticals are produced using mammalian cells which often require serum when cultured in vitro. Since the use of serum involves many ethical, safety and scientific complications, a high-producing NS0 transfectoma which was isolated using Clone Pix FL system, was directly adapted to serum-free growth media (SFGM) in T75 flasks. This transfectoma has been engineered to stably secrete humanized anti-C2 monoclonal antibody (hum-C2 mab) which is highly specific for a colorectal tumor associated antigen. However, the serum-independent NS0 transfectoma had low cell viability when cultured in spinner flasks. Therefore, triple flasks were used instead. The growth characteristics and also hum-C2 mab productivity were comparable between cells cultured in serum-free and serum-supplemented media. Besides that, an automated liquid chromatography system, Äktaprime Plus, was used to purify hum-C2 mab from filtered and concentrated cell culture supernatant since the conventional method of antibody purification is time-consuming, laborious and prone to errors. The high-throughput nature of Äktaprime Plus enabled the purification hum-C2 mab in less than 30 minutes. In addition, the real-time monitoring and the automated fraction collection of Äktaprime Plus eliminated the need for downstream analysis and decreased the risk of spillage or misplacing of fractions containing precious hum-C2 mab. To evaluate the functionality of hum-C2, a conventional antigen-based ELISA could not be used due to the lack of commercially-available purified C2 antigen. As an alternative, a cell-based ELISA was performed using SW1116 cells and even after humanization, the purified hum-C2 mab was still able to bind to the C2 antigen expressed on the surface of SW1116 cells. In summary, the production of NS0 transfectoma in SFGM using triple flasks and the convenient one-step affinity chromatography using Äktaprime Plus resulted in hum-C2 mab being free from exogenous protein contamination especially from bovine polyclonal antibodies found in serum. From the cell-based ELISA, cell binding was observed which confirms the functionality of purified hum-C2 mab after humanization.